The Influence of School Work Climate and Work Motivation on the Teaching Productivity of Elementary School Teachers in Cimanuk District - Nur Ida Apriani; Cucu Atikah; Fadlullah Fadlullah (Assyfa Journal of Islamic Studies, 2026)
This research is motivated by the suboptimal teaching productivity of elementary school teachers in Cimanuk District, Pandeglang Regency, which is suspected to be influenced by the school's work climate and teacher work motivation. This study aims to analyze the influence of work climate and work motivation on teacher teaching productivity, both partially and simultaneously. This study uses a quantitative approach with a survey method. The study population was all elementary school teachers in Cimanuk District, Pandeglang Regency, with a sampling technique using proportional random sampling. Data collection was carried out through questionnaires that have been tested for validity and reliability. Data analysis techniques used simple linear regression and multiple linear regression with the help of the SPSS program. This study is expected to show that work climate has a positive and significant effect on teacher teaching productivity, work motivation has a positive and significant effect on teacher teaching productivity, and work climate and work motivation simultaneously have a positive and significant effect on teacher teaching productivity. Thus, improving a conducive work climate and high work motivation can increase the teaching productivity of elementary school teachers in Cimanuk District, Pandeglang Regency.